Feasibility of Race by Sex Intersectionality Research on Suicidality in the Adolescent Brain Cognitive Development (ABCD) Study - Assari, Shervin (Children (Basel), 2021)
Intersectional research on childhood suicidality requires studies with a reliable and valid measure of suicidality, as well as a large sample size that shows some variability of suicidality across sex by race intersectional groups. Objectives: We aimed to investigate the feasibility of intersectionality research on childhood suicidality in the Adolescent Brain Cognitive Development (ABCD) study. We specifically explored the reliability and validity of the measure, sample size, and variability of suicidality across sex by race intersectional groups. Methods: We used cross-sectional data (wave 1) from the ABCD study, which sampled 9013 non-Hispanic white (NHW) or non-Hispanic black (NHB) children between the ages of 9 and 10 between years 2016 and 2018. Four intersectional groups were built based on race and sex: NHW males (n = 3554), NHW females (n = 3158), NHB males (n = 1164), and NHB females (n = 1137). Outcome measure was the count of suicidality symptoms, reflecting all positive history and symptoms of suicidal ideas, plans, and attempts. To validate our measure, we tested the correlation between our suicidality measure and depression and Child Behavior Checklist (CBCL) sub-scores. Cronbach alpha was calculated for reliability across each intersectional group. We also compared groups for suicidality. Results: We observed some suicidality history in observed 3.2% (n = 101) of NHW females, 4.9% (n = 175) of NHW males, 5.4% (n = 61) of NHB females, and 5.8% (n = 68) of NHB males. Our measure’s reliability was acceptable in all race by sex groups (Cronbach alpha higher than 0.70+ in all intersectional groups). Our measure was valid in all intersectional groups, documented by a positive correlation with depression and CBCL sub-scores. We could successfully model suicidality across sex by race groups, using multivariable models. Conclusion: Given the high sample size, reliability, and validity of the suicidality measure, variability of suicidality, it is feasible to investigate correlates of suicidality across race by sex intersections in the ABCD study. We also found evidence of higher suicidality in NHB than NHW children in the ABCD study. The ABCD rich data in domains of social context, self-report, schools, parenting, psychopathology, personality, and brain imaging provides a unique opportunity to study intersectional differences in neural circuits associated with youth suicidality.